2016
DOI: 10.1037/a0039467
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage: Military sexual trauma and help-seeking barriers.

Abstract: Objective: Military Sexual Trauma (MST) can be a harmful aspect of military life. Despite the availability of resources, Service members may encounter barriers that impede help-seeking for sexual assault (i.e., encountering logistical constraints, anticipating stigma). We examined how such barriers undermine wellbeing (i.e., exacerbate symptoms of depression and posttraumatic stress disorder [PTSD]) among MST survivors, both women and men. Additionally, we investigated how these barriers aggravate depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…The 2010 Workplace and Gender Relations Survey of Active Duty Members was utilized to measure MST among LGBT military personnel (Holland, Rabelo, & Cortina, 2016; Rock, Lipari, Cook, & Hale, 2010). Participants were asked to complete 19 items on the frequency of sexual harassment and sexual assault experienced within the past 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The 2010 Workplace and Gender Relations Survey of Active Duty Members was utilized to measure MST among LGBT military personnel (Holland, Rabelo, & Cortina, 2016; Rock, Lipari, Cook, & Hale, 2010). Participants were asked to complete 19 items on the frequency of sexual harassment and sexual assault experienced within the past 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…18,25,26 Social barriers may also impede treatment engagement, some of which may be particularly salient to individuals who have experienced a sexual trauma. For instance, veterans have described fears of being judged for seeking therapy and/or for disclosing their trauma, 14,27 as well as a fear that providers and institutions may not believe their report of experiencing MST. 14,27,28 Veterans have also reported feeling betrayed by military affiliated institutions, which are perceived to have cultivated and/or perpetuated an environment in which MST could occur.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, veterans have described fears of being judged for seeking therapy and/or for disclosing their trauma, 14,27 as well as a fear that providers and institutions may not believe their report of experiencing MST. 14,27,28 Veterans have also reported feeling betrayed by military affiliated institutions, which are perceived to have cultivated and/or perpetuated an environment in which MST could occur. 28 This may impede engagement in services due to mistrust of institutions that are supposed to provide protection.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to care within both the military and VA health care systems may prolong the time an individual takes to seek treatment for MST-related health problems. Recent research has also indicated that perceived barriers to help-seeking following military sexual assault, particularly those related to logistical factors (e.g., difficulty getting time off work) and stigma (e.g., being perceived as weak), may contribute to the risk of experiencing depressive or PTSD symptoms (Holland, Rabelo, & Cortina, 2015). In addition, it may take years for one to recognize an incident as sexual trauma, and in some cases, a fragmented memory of the event may delay acknowledgment even more .…”
Section: Discussionmentioning
confidence: 99%
“…Efforts should be made in increasing accessibility and acceptability of immediate care for victims of sexual trauma in the military. The ability to and likelihood of seeking mental health care while in the military are dependent on a range of individual and environmental characteristics, but previously noted barriers have largely related to stigma surrounding mental health, concerns about the impact on one's military career, and tenets of military culture which encourage "toughness" and stoicism (Eckart & Dufrene, 2015;Greene-Shortridge, Britt, & Castro, 2007;Holland et al, 2015;Mengeling, Booth, Torner, & Sadler, 2015). For military victims of sexual trauma, these barriers may be compounded by the need to report the trauma in order to receive treatment, as well as concerns about confidentiality and retaliation (Burns, Grindlay, Holt, Manski, & Grossman, 2014).…”
Section: Discussionmentioning
confidence: 99%